Penerapan Media Literasi Karikatur dalam Pengajaran Bahasa bagi Siswa TPQ Al-Hidayah Kelurahan Meruyung Limo Depok - Atmapratiwi, Heppy; Wiyanti, Endang; Sudrajat, Yayan (Presisi Jurnal Pengabdian Masyarakat, 2023)
The purpose of community service is to socialize and improve literacy skills in student in order to produce optimal results due to the lack of assistance and training to increase awareness and literacy skills.  Through initial observations and interviews with the Foundation, it was revealed that the students had not fully understood the importance of language literacy in the context of global communication, which resulted in a lack of maturity in oral culture. Therefore, this community service activity aims to enable the students of TPQ Al-Hidayah to integrate language literacy in daily life, increase community knowledge through access to information, and develop a positive attitude towards the interpretation of the information obtained. The results of this service activity include the preparation of materials or studies to help students understand and apply language literacy and measure the learning outcomes of these literacy skills. In addition, the team will create a published article to convey the achievements of this abdimas activity to the wider community, with the hope that the information disseminated can provide significant benefits. Thus, this effort is expected to make an effective contribution in overcoming social problems, especially the education gap in society.